The effect of Neurofeedback Training on Working Memory and Perceptual-Motor Development in Athlete Boys - Amir Dana; Saleh Rafiee; Amin Gholami (Shiraz University of Medical Sciences, 2019)
Background: This research aims to study the effect of neurofeedback training on the working memory and perceptual-motor development of athlete boys. Methods: Thirty athlete boy students of Gorgan province were selected by convenient sampling and participated in the research process. First, a pretest was conducted. All participants had done Wechsler digit span test and Lincoln- Oseretsky perceptual-motor capabilities test. After that, participants were randomly divided into test and control groups. Subjects of the experiment group had 12 one-hour sessions neurofeedback training while the control group subjects received no intervention during this time. Data were analyzed by using multivariate covariance test (MANCOVA) by SPSS 18. Results: The results of data analysis showed that there is a significant relationship between mean direct and reverse digit span numbers and perceptual-motor development of the experiment group before and after treatment (P<0.05) and neurofeedback training has positive effect on the working memory and perceptual-motor development of athlete boys. Conclusion: Regarding the results of the current research, it seems that neurofeedback training is effective on the working memory and perceptualmotor development of athlete boys; however, more research is required to achieve more definite results about the effective and perpetual effects of neurofeedback on the cognitive function of people.